HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN SERVIS ATAS TIM BOLA VOLI MAN 1 KAMPAR KECAMATAN KUOK - Joko Suprianto; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The low services of top serve blow from students might be due to the lacks of tightness on the arm and shoulder muscles which is causes the ball do not enter or exit the volleyball court. This is based on observation by researiler when they practice and has are match. The purpose of this research was to find out the correlation of arm and shoulder muscle strength on volleyball team MAN 1 Kampar in kuok District. The population for these research is 17 people. By using the total sampling technique, the sample was 17 people. The instrument that used in this research is Expanding Dynamometer and service results. All the data obtained was analyzed using product moment correlation. Based on the results of the analysis and discussion in the previous section, conclusions and recommendations can be drawn in this section, namely the strength of the arm and shoulder muscles associated with the results of serving volleyball in sports volleyball MAN 1 Kampar in Kuok district. The results of the analysis show that r count> r table at α = 0.05Key Words : Strength of arm and shoulder muscles, result of serving.